2017
DOI: 10.1016/j.eurpsy.2017.01.1188
|View full text |Cite
|
Sign up to set email alerts
|

Mental flexibility and problem solving in adult patients who present non-suicidal self-injury

Abstract: IntroductionNon-Suicidal Self-Injury (NSSI) is considered a dysfunctional way of dealing with problem situations.ObjectiveThis study aimed to investigate the problem solving capacity in adults with NSSI compared to controls.MethodsThirty-three patients who sought treatment for NSSI (NSSI group) were compared with 33 individuals without psychiatric disorder (control group). We also investigated Axis I disorders, executive functions and problem solving capacity.ResultsIn both groups, the majority were women (77.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Previous studies on EF and DSH have highlighted inhibition and working memory as topics of interests, although cognitive flexibility also has been explored (Drabble et al, 2014;Garreto et al, 2017;Miranda et al, 2012). The results from the present study differ from Fikke et al (2011) results, since they indicate that the domain of cognitive flexibility is primarily affected, and not working memory.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Previous studies on EF and DSH have highlighted inhibition and working memory as topics of interests, although cognitive flexibility also has been explored (Drabble et al, 2014;Garreto et al, 2017;Miranda et al, 2012). The results from the present study differ from Fikke et al (2011) results, since they indicate that the domain of cognitive flexibility is primarily affected, and not working memory.…”
Section: Discussioncontrasting
confidence: 96%
“…In a related study, Miranda et al (2012) found that cognitive inflexibility predicted suicidal ideation in a population of individuals with previous suicidal behavior. Also, in a comparison between patients who sought treatment for NSSI and a non-psychiatric comparison group, Garreto et al (2017) found that the NSSI-group showed significantly lower problemsolving capacity and mental flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of suicidal brains have found that the changes in brain structure and function associated with suicide are mainly in the orbitofrontal and dorsolateral parts of the PFC, which are the control systems of EF such as cognitive inhibition [ 70 ]. Studies have revealed that the EF of adolescents with NSSI—specifically flexibility and high-risk decision-making—is significantly different from that of non-NSSI adolescents [ 71 , 72 ]. Deficiencies in problem-solving capacity may indicate low mental flexibility in people with self-injury [ 71 ].…”
Section: Discussionmentioning
confidence: 99%